2000
DOI: 10.1046/j.1439-0450.2000.00313.x
|View full text |Cite
|
Sign up to set email alerts
|

Carcass Quality in Certified Organic Production Compared with Conventional Livestock Production

Abstract: By studying carcass quality, expressed as affection, pathological findings, slaughter-weight and evaluation, a picture of an animal's health and potential as high quality food is achieved. This study compares the carcass quality in Swedish certified organic meat production with that of conventional meat production slaughtered during 1997. The study involves 3.9 million pigs, about 570,000 cattle and 190,000 sheep, all reared conventionally and 3483 pigs 4949 cattle and 4997 sheep reared according to organic st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
61
0
7

Year Published

2005
2005
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(72 citation statements)
references
References 1 publication
4
61
0
7
Order By: Relevance
“…All other genotypes show a decrease in meat percentage close to 1% except the Du 3 DL animals with 2.6% lower meat percentage under organic conditions. In another study, 0.6% less lean meat was observed under organic conditions (Hansson et al, 2000). Assuming that in the latter study not all pigs were fed ad libitum to the final weight, the higher decrease in this study under ad libitum feeding till the end was expected.…”
Section: Resultsmentioning
confidence: 46%
“…All other genotypes show a decrease in meat percentage close to 1% except the Du 3 DL animals with 2.6% lower meat percentage under organic conditions. In another study, 0.6% less lean meat was observed under organic conditions (Hansson et al, 2000). Assuming that in the latter study not all pigs were fed ad libitum to the final weight, the higher decrease in this study under ad libitum feeding till the end was expected.…”
Section: Resultsmentioning
confidence: 46%
“…It is acknowledged that meat from cows and sheep contains less fat when animals are fed with grass rather than concentrate. In that line, a study conducted in Sweden showed that organically-bred cows have more lean meat than their conventional counterparts (Hansson et al, 2000). This was not found in pigs (Sundrum et al, 2000).…”
Section: Macronutrient Contentsmentioning
confidence: 96%
“…For lipids, few studies have compared the total lipid content of beef, pork or chicken meat (Pastsshenko et al, 2000;Hansson et al, 2000;Hönikel, 1998;Fischer, 2001;Castellini et al, 2002). It is acknowledged that meat from cows and sheep contains less fat when animals are fed with grass rather than concentrate.…”
Section: Macronutrient Contentsmentioning
confidence: 99%
“…In an intensive as well as in an outdoor pig production unit, several animal welfare problems such as tail-biting and belly nosing have been recognised (Hansson et al, 2000;Walker and Bilkei, 2006), which points out that at least some animals cannot cope with the environment. To the awareness of the authors, there is a lack of data concerning the measurement of the relationship between behavioural and physiological characteristics under fearinduced situations in pigs.…”
Section: Introductionmentioning
confidence: 99%